Otoritas Wilayatul Hisbah dalam Pemerintahan: (Suatu Kajian terhadap Penegakan dan Pengawasan Hukum Islam di Aceh) - Abdullah, Asnawi; Safriadi, Safriadi (Syarah: Jurnal Hukum Islam dan Ekonomi, 2022)
This research wants to discuss about “wilayatul hisbah” authority in government. A review of the enforcement and supervision of law in Aceh. In this study, the authors use the library research (library research), and data collection is done by reviewing the literature that relates to wilayatul hisbah and other books related to the discussion of this study as a secondary material, so that the pattern is in the form of qualitative. In addition, the analysis by the writer is descriptive analysis. From the results of this study found the conclusion that the authorities Wilayatul Hisbah (WH) in government in a historical perspective covering prevent unjust enjoining enforcement and supervision. Wilayatul Hisbah (WH) is one of the judiciary in the government system, and is an official institution established by the government of the Islamic state. Hisbah region oversees things seem (Zahir) and already ma'ruf in the community. In addition to overseeing, Hisbah region also has the authority to sentence those who violated the Shari'ah. While authorities Wilayatul Hisbah (WH) in the context of the Aceh government can be detailed as follows: first, To supervise the implementation and violations of laws and regulations in the field of Islamic Shari'ah, both friendly, spiritual guidance and advocacy against any person based on preliminary evidence worth is alleged to have violated the laws and regulations in the field of Islamic shariah. Third, Slate advised, prevent and prohibit any person who should presumably have been, are or will be in violation of the laws and regulations in the field of Islamic Shari'ah. fourth, Bestows case a violation of legislation in the field of Islamic Shari'ah to investigator.